Pediatric Medulloblastoma – Update on Molecular Classification Driving Targeted Therapies - DeSouza, Ruth-Mary; Jones, Benjamin R. T.; Lowis, Stephen P.; Kurian, Kathreena M. (Frontiers in Oncology, 2014)
As advances in the molecular and genetic profiling of paediatric medulloblastoma evolve, associations with prognosis and treatment are found (prognostic and predictive biomarkers) and research is directed at molecular therapies. Medulloblastoma typically affects young patients, where the implications of any treatment on the developing brain must be carefully considered. The aim of this article is to provide a clear comprehensible update on the role molecular profiling and subgroups in paediatric medulloblastoma as it is likely to contribute significantly towards prognostication. Knowledge of this classification is of particular interest because there are new molecular therapies targeting the Shh subgroup of medulloblastomas.